Laboratories of history The archive centrality in Cecília Westphalen´s professional trajectory - Machado, Daiane Vaiz [UNESP] (My University, 2019)
The article problematizes the professionalization of historical research in the Brazilian university, strengthened between the 1960s and 1970s, regarding the relationship between historiographical making and the access to documentary sources. Therefore, our fountainhead is the historian Cecília Westphalen performance in creating projects field and methodologies for surveying and files enrollment.
Laboratorios de historia La centralidad del archivo en el camino profesional de Cecília Westphalen
laboratórios da história a centralidade do arquivo na trajetória profissional de cecília westphalen
Keywords: archives; Brazilian historiography; Cecília Westphalen; historical research